Contemporary Ulama's Perspectives on Contraception in Modern Families: A Comparative Analysis of Yusuf al-Qaradawi and Ibn Utsaimin - Ade Faizah; Abdul Manan; Nufiar Nufiar (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2026)
The use of contraception in Muslim families remains a debated issue among contemporary Islamic scholars, particularly in response to changing social conditions, reproductive health concerns, and the evolving dynamics of modern family life. Previous studies have generally examined contraception from normative Islamic legal perspectives, while comparative analyses of the views of Yusuf al-Qaradawi and Ibn Utsaimin remain relatively limited. Therefore, this study aims to comparatively analyze the legal reasoning, methods of legal interpretation (istinbāṭ), and contemporary relevance of the views of both scholars regarding the use of contraception in modern Muslim families. This study employs a qualitative library research method using a descriptive-comparative approach. Data were collected from classical and contemporary Islamic legal literature, fatwas, scholarly publications, and academic studies related to family planning and reproductive ethics in Islam. The data were analyzed using comparative content analysis to identify the similarities, differences, and underlying methodological foundations of the two scholars' perspectives. The findings reveal that both Yusuf al-Qaradawi and Ibn Utsaimin permit the use of temporary contraception under specific conditions, particularly to protect maternal health, ensure child welfare, and maintain family stability. However, they differ significantly in their legal methodologies. Yusuf al-Qaradawi adopts a more contextual approach based on maqāṣid al-sharīʿah and public welfare (maṣlaḥah), whereas Ibn Utsaimin applies a more textual and precautionary approach by adhering closely to scriptural evidence. This study contributes to the development of contemporary Islamic family law by demonstrating how different methods of legal interpretation shape Islamic legal responses to modern reproductive issues. The findings also provide valuable insights for scholars, policymakers, and family planning practitioners in formulating reproductive health policies that are consistent with Islamic legal principles while remaining responsive to the needs of modern Muslim families.